2010
DOI: 10.1007/s12035-009-8096-6
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Sphingolipid Metabolism and Membrane Organization in Neurodegenerative Disorders

Abstract: Sphingolipids are polar membrane lipids present as minor components in eukaryotic cell membranes. Sphingolipids are highly enriched in nervous cells, where they exert important biological functions. They deeply affect the structural and geometrical properties and the lateral order of cellular membranes, modulate the function of several membrane-associated proteins, and give rise to important intra- and extracellular lipid mediators. Sphingolipid metabolism is regulated along the differentiation and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 326 publications
1
79
0
Order By: Relevance
“…While mechanisms of preferential elevation of GM2 in phagocytic microglia in WT mice remain to be elucidated, accumulation of simple gangliosides, such as GM3 and GM2, have often been reported in lysosomal storage diseases, neurodegenerative diseases, and neuroinjury models ( 23, 27-29, 34-36, 50, 51 ). Even when a primary defi ciency in a lysosomal glycohydrolase, activator protein, or saposin directly involved in the degradation of GM2 or GM3 ( 52 ) is not present, the accumulation of GM2/GM3 appears to occur, at least in part, in the endosomal/lysosomal system ( 26,29,30,34,53 ) and/or in lipid rafts ( 24,27,33 ). As well as for defi ciencies in catabolic proteins not directly involved in degradation of these gangliosides, defects in traffi cking of gangliosides from endosomes to the Golgi apparatus ( 53,54 ) or from late endosomes to lysosomes ( 55,56 ) also observed in some lysosomal storage diseases can produce similar accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mechanisms of preferential elevation of GM2 in phagocytic microglia in WT mice remain to be elucidated, accumulation of simple gangliosides, such as GM3 and GM2, have often been reported in lysosomal storage diseases, neurodegenerative diseases, and neuroinjury models ( 23, 27-29, 34-36, 50, 51 ). Even when a primary defi ciency in a lysosomal glycohydrolase, activator protein, or saposin directly involved in the degradation of GM2 or GM3 ( 52 ) is not present, the accumulation of GM2/GM3 appears to occur, at least in part, in the endosomal/lysosomal system ( 26,29,30,34,53 ) and/or in lipid rafts ( 24,27,33 ). As well as for defi ciencies in catabolic proteins not directly involved in degradation of these gangliosides, defects in traffi cking of gangliosides from endosomes to the Golgi apparatus ( 53,54 ) or from late endosomes to lysosomes ( 55,56 ) also observed in some lysosomal storage diseases can produce similar accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that while GM2 is normally a minor ganglioside in the nervous system, it is transiently elevated during a restricted period of brain development ( 22 ) and signifi cantly elevated not only in the brain of GM2 gangliosidosis, but also in the brain of other lysosomal storage disorders such as Niemann-Pick C disease, mucolipidosis IV, and mucopolysaccharidoses (23)(24)(25)(26)(27)(28)(29)(30). In addition, accumulation of GM2 has been observed in neurodegenerative diseases such as Alzheimer disease (31)(32)(33) and Angelmanlike syndrome ( 34 ), and in rodent acute brain injury models such as blast-induced mild traumatic brain injury ( 35 ) and a transient focal cerebral ischemia model ( 36 ).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…This property of SNCA to form amyloid fibrils is thought critical for the development of neurotoxicity (Mazzulli et al, 2011). The lipids which accumulate as a result of deficiencies in GCase could alter the sphingolipid composition of membranes and prevent the membrane binding of SNCA, thereby enhancing its aggregation in the cytoplasm (Piccinini et al, 2010).…”
Section: Altered Lipid Metabolismmentioning
confidence: 99%
“…Not surprisingly, several pieces of evidence indicate a biunivocal relationship between nervous system dysfunction and altered SL metabolism [74]. Inherited disorders caused by defects in SL metabolism are characterized by acute brain involvement [75]; this is the case of several lysosomal storage diseases, due to defects in SL catabolism (that will be discussed in detail below).…”
Section: Sphingolipids In Nervous System Physiology and Pathologymentioning
confidence: 99%